The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.cell.2006.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore Orientation during Meiosis Is Controlled by Aurora B and the Monopolin Complex

Abstract: Kinetochores of sister chromatids attach to microtubules emanating from the same pole (coorientation) during meiosis I and microtubules emanating from opposite poles (biorientation) during meiosis II. We find that the Aurora B kinase Ipl1 regulates kinetochore-microtubule attachment during both meiotic divisions and that a complex known as the monopolin complex ensures that the protein kinase coorients sister chromatids during meiosis I. Furthermore, the defining of conditions sufficient to induce sister kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
176
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(190 citation statements)
references
References 45 publications
11
176
1
1
Order By: Relevance
“…Although the molecular mechanisms that distinguish these two modes of attachment are incompletely understood, monopolar attachment is associated with cohesin binding at the core centromere (23), and the need for the monopolin complex to direct this binding has been suggested (24). Monje-Casas et al (25) reported that the mitotic expression of the normally meiosis-specific monopolin complex was sufficient to direct meiosis I-like segregation of mitotic chromosomes. Thus, one possible scenario is that a small subset of mitotic cells expresses the meiotic proteins that allow monopolar kinetochore attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the molecular mechanisms that distinguish these two modes of attachment are incompletely understood, monopolar attachment is associated with cohesin binding at the core centromere (23), and the need for the monopolin complex to direct this binding has been suggested (24). Monje-Casas et al (25) reported that the mitotic expression of the normally meiosis-specific monopolin complex was sufficient to direct meiosis I-like segregation of mitotic chromosomes. Thus, one possible scenario is that a small subset of mitotic cells expresses the meiotic proteins that allow monopolar kinetochore attachment.…”
Section: Discussionmentioning
confidence: 99%
“…During meiosis I, sister chromatid cohesion is preserved at centromeres of monocentric chromosomes and at the long arm of holocentric chromosomes, whereas cohesion is released along chromatid arms of monocentric chromosomes and the short arm of holocentric bivalents. In monocentric organisms, Aurora B promotes preservation of cohesion at centromeres (Monje-Casas et al, 2007;Resnick et al, 2006;Yu and Koshland, 2007). By contrast, in worms, AIR-2/Aurora B functions to promote cohesion release at the short arm (Kaitna et al, 2002;Rogers et al, 2002).…”
Section: Condensin I and Chromosomal Passengersmentioning
confidence: 99%
“…8). On monocentric chromosomes, Aurora B is needed for coorientation of sister kinetochores and biorientation of kinetochores of homologs by destabilizing improper kinetochore-microtubule attachments at the centromeres (Hauf et al, 2007;Monje-Casas et al, 2007). In holocentric organisms, such as C. elegans, localized centromeres are lacking, and instead the location of crossover determines which end of the chromosome will form the short arm of the bivalent (Nabeshima et al, 2005), which in turn determines the plane of chromosome orientation (Albertson and Thomson, 1993;Wignall and Villeneuve, 2009).…”
Section: Condensin I and Chromosomal Passengersmentioning
confidence: 99%
“…We also analyzed whether, as observed for mammalian cells (21), increased Aurora B activity leads to aneuploidy in yeast. To this end, we followed chromosome segregation using cells with chromosome 4 tagged with GFP at the centromere (CrIV-GFP) (25). In wild-type anaphase cells, two separate DNA masses of approximately equal size, each containing a fluorescent GFP dot, could be distinguished in the mother and daughter cells once the sister chromatids segregated toward opposite spindle poles (Fig.…”
Section: Overexpression Of Ipl1 and Sli15 Leads To Severe Problems Inmentioning
confidence: 99%